2018
DOI: 10.18632/oncotarget.25038
|View full text |Cite
|
Sign up to set email alerts
|

The use of long non-coding RNAs as prognostic biomarkers and therapeutic targets in prostate cancer

Abstract: Prostate cancer is the most common cancer in men and the second leading cause of cancer-related deaths. The most used biomarker to detect prostate cancer is Prostate Specific Antigen (PSA), whose levels are measured in serum. However, it has been recently established that molecular markers of cancer should not be based solely on genes and proteins but should also reflect other genomic traits; long non-coding RNAs (lncRNAs) serve this purpose. lncRNAs are transcripts of >200 bases that do not encode proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 139 publications
1
27
0
Order By: Relevance
“…Though treatable, definitive understanding about the molecular origins of prostate cancer is lacking, and there is considerable controversy about screening methods (1)(2)(3)(4)(5)(6). Continued efforts to identify molecular markers that distinguish between tumors that will remain latent, progress slowly, or progress aggressively are needed (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Though treatable, definitive understanding about the molecular origins of prostate cancer is lacking, and there is considerable controversy about screening methods (1)(2)(3)(4)(5)(6). Continued efforts to identify molecular markers that distinguish between tumors that will remain latent, progress slowly, or progress aggressively are needed (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Long non–coding RNAs are largely recognized as important players in cancer disease [ 7 , 51 ], including haematological malignancies [ 16 , 52 , 53 ]. In addition, considering that lncRNA expression is tightly controlled and exhibits even higher cell specificity than proteins, lncRNAs are emerging as a promising class of biomarkers and/or potential therapeutic targets [ 54 , 55 , 56 , 57 ]. Indeed, several lncRNA signatures for different tumours such as large–B–cell lymphoma, ovarian cancer, breast cancer and other oncological diseases have been reported [ 12 , 13 , 14 , 37 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Studies used lncRNA microarrays or RNA-sequencing to discover promising lncRNAs in ESCC. In addition, researchers have revealed that lncRNAs can be used as potential diagnostic biomarkers for esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Even, lncRNAs could predict the prognosis of many malignancies. [12][13][14][15] Studies used lncRNA microarrays or RNA-sequencing to discover promising lncRNAs in ESCC. 16,17 However, these studies revealed different lncRNAs.…”
Section: Discussionmentioning
confidence: 99%